1996
DOI: 10.1038/bjc.1996.594
|View full text |Cite
|
Sign up to set email alerts
|

Allele loss from large regions of chromosome 17 is common only in certain histological subtypes of ovarian carcinomas

Abstract: Summary Using a panel of ten polymorphic markers, we examined the frequency of loss of heterozygosity (LOH) on chromosome 17 in 55 sporadic ovarian tumours. LOH on 17p and 17q was observed to be 50% and 62% respectively. LOH at D17S5 was detected in 24/36 (67%) of malignant cases and in 19/43 (44%) at TP53; the marker D17S855 intragenic to the BRCAJ gene showed allele loss in 50% (20/40) cases. The data presented here suggest that loss of the whole chromosome 17 is a relatively frequent event (30%) in ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
16
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…While Pierretti et al (1995) reported an overall di erence in LOH of 17p versus 17q markers in endometrioid and mucinous tumors, the LOH patterns displayed by each tumor type was not described and therefore comparisons with the present study cannot be made. The observation by Papp et al (1996) that LOH across multiple chromosome 17q alleles is infrequent in tumors of endometrioid, mucinous and clear cell histology are comparable with those described in the present study. However, LOH patterns observed for the endometrioid and mucinous tumors di ered.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While Pierretti et al (1995) reported an overall di erence in LOH of 17p versus 17q markers in endometrioid and mucinous tumors, the LOH patterns displayed by each tumor type was not described and therefore comparisons with the present study cannot be made. The observation by Papp et al (1996) that LOH across multiple chromosome 17q alleles is infrequent in tumors of endometrioid, mucinous and clear cell histology are comparable with those described in the present study. However, LOH patterns observed for the endometrioid and mucinous tumors di ered.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the frequent LOH of TP53 accompanying LOH of all informative 17q loci suggests that complete loss of an entire chromosome 17 homolog is a frequent event in epithelial ovarian cancer. The high frequency of LOH of 17q loci is in line with the independent reports demonstrating a frequent LOH (ranging from 30 to 89%) of all polymorphic markers on chromosome 17 (Foulkes et al, 1993;Tavassoli et al, 1993;Pieretti et al, 1995;Papp et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations